The Unintended Consequence of Stringent Immigration Enforcement on Staffing in Nursing Homes: Evidence from Secure Communities - Christian Gunadi (Global Labor Organization (GLO), 2023)
The provision of healthcare in the United States is increasingly more reliant on immigrant workers. In this paper, I examine the impact of Secure Communities, a major immigration enforcement program that was designed to check the immigration status of all individuals arrested by local police, on staffing in nursing homes. Using difference-in-differences strategy that exploits staggered activation of Secure Communities across U.S counties, I found that the program reduced direct-care staff hours per resident day by 0.082, an approximately 2.2% decline relative to the mean of treatment counties in the baseline period. This finding suggests that stringent immigration enforcement may exacerbate the healthcare worker shortage in the United States.
Keywords: K37; J61; I11; J2; J15; 330; Staffing; Nursing Homes; Secure Communities; Immigration